Measuring and improving infrastructure performance (Studies in infrastructure technology and policy., 1995)
The nation's physical infrastructure facilitates movement of people and goods; provides safe water; provides energy when and where needed; removes wastes; enables rapid communications; and generally supports our economy and quality of life. Developing a framework for guiding attempts at measuring the performance of infrastructure systems and grappling with the concept of defining good performance are the major themes of this book. Focusing on urban regions, within a context of national policy, the volume provides the basis for further in-depth analysis and application at the local, regional, state, and national levels.